Association of Rhomboid Muscle Spasm and Neck Pain among Occupational Bike Riders - RINADMUNNAN,; BAZAL BUKHARI, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Occupational bike riders, who spend extensive hours riding and navigating through traffic, are especially prone to developing muscle spasms and neck pain. The rhomboid muscles, located between the shoulder blades, play a crucial role in stabilizing the shoulder blades and maintaining proper posture. Aim: To find the association of rhomboid muscle spasm and neck pain among occupational bike riders. Methods: This cross-sectional study was conducted among occupational bike riders in Lahore over a duration of four months. The study population consisted of 100 male riders aged 18-40 years, who completed at least 10 rides daily. Non-probability convenient sampling was employed. Data was collected using the Neck Disability Index (NDI) and the Numeric Pain Rating Scale. Data analysis was performed using SPSS version 25. Results: The results showed a mean age of 28.92±6.81 years. The Neck Disability Index results indicated that 3.4% reported no disability, 18.1% mild disability, 50% moderate disability, 25.9% severe disability, and 2.6% complete disability. Pain intensity ratings revealed that 9.5% experienced no pain, 19% mild pain, 39.7% moderate pain, 28.4% severe pain, and 3.4% reported the worst imaginable pain (p = 0.021). Conclusion: Current study concluded that in occupational bike riders there is association of rhomboid muscle spasm and neck pain among occupational bike riders indicates a significant prevalence of musculoskeletal issues within this population. The findings suggest that frequent and prolonged riding contributes to increased muscle tension and spasms in the rhomboid region, which correlates strongly with reported neck pain. Keywords: Rhomboid muscle spasm, neck pain, occupational bike riders, neck disability index, musculoskeletal issues